Suicide attempt of young woman by Propafenone overdose - case report - Wais, Marcin; Gruca, Dariusz; Zając, Marlena (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Over the last few years, the number of suicide attempts in Polish women has been steadily increasing. This report presents a case of a 18 years old woman hospitalized in the Toxicology and Cardiology Department due to poisoning with antiarrhythmic drug – Propafenone, taken for suicide purpose. Brief description of the state of knowledge: Propafenone is an antiarrhythmic drug which belongs to class IC according to the Vaughan-Williams classification. The overdose of this drug can cause various symptoms and complications such as cardiac arrhythmias, liver damage, cardiac arrest and even death. This drug has no specific antidote. Conclusions: Propafenone poisoning is a significant clinical challenge and the consequences are often unpredictable and life-threatening. Treatment options such as natrium bicarbonicum, insulin, intravenous lipid emulsion, calcium gluconate seem to be good choices and the effects of treatment with these drugs are promising for the future.